Analysis of the Water Vapor Characteristics and Trigger Mechanism for a Typical Heavy Rainstorm in the Extreme Arid Region of the Southern Xinjiang - Shaoqing MO; Yaohui LI (Gaoyuan qixiang)
In order to strengthen our understanding of the water vapor characteristics and trigger mechanism of the rainstorm in southern Xinjiang， this paper analyzes a rainstorm process occurred over southern Xinjiang region during 24 -28 June 2019.Various data includingFNL（NCEP final operational global analysis） and ERA5 （fifth version of the European Centre for medium-range weather forecasts reanalysis model） reanalysis data， hourly observation data at the automatic meteorological station， the satellite equivalent blackbody brightness temperature data of FY-2G are used.The results show that the precipitation occurred under the background of synoptic circulation with “two-ridge and two-trough” pattern over the middle and high latitude， the low vortex of Balkhash Lake， the ridge of Iran and convergence line are the main weather systems leading to the heavy rainfall.The water vapor of the heavy rainfall mainly comes from the Atlantic Ocean， Black Sea， Rio / Aral Sea， Arabian Sea and Gulf of Bengal， along the northwest， partial west and southwest paths to the southern Xinjiang Basin.Water vapor from the northwest and west paths to the southern Xinjiang Basin are guided by the low-level jet， and from the southwest path is transported over the Qinghai-Xizang Plateau to the southern Xinjiang under the guidance of the 500 hPa cyclone wind field and the southwest high-level jet on 200 hPa in the western southern Xinjiang.Water vapor revenue and expenditure calculation shows that water vapor input is mainly concentrated on the high level of troposphere at the south boundary， low and high levels of troposphere at the north boundary； the output of water vapor is concentrated in the low and high layers of the troposphere at the east boundary.The convergence line is the most important trigger system for this heavy rainfall， whose form is caused by the convergence of the dominant air flow invaded from the north in front of the high and steep terrain （KunLun Mountains） on the south side of the southern Xinjiang Basin.Meanwhile， the accumulation of water vapor brought by the northwesterly airflow in the north of the convergence line in front of the mountain is sufficient which is favorable for the rainstorm.Under the impact of terrain uplift， accompanied with the uplifting of air mass and accumulation of water vapor at the foothill of KunLun mountains， unstable energy is released and the convection system constantly generates and develops near the mountains， bringing continuous heavy rainfall to Hotan region.